Socio-economic Characteristics and Their Effect on Smallholder Farmers’ Decisions to Participate in a Communal Land Restoration Project in Central Ethiopia - Hinde, Omer; Beyera, Gizachew; Hailu, Hiwot; Limenih , Beliyu; N. Ayana , Alemayehu (BPFP Universitas Bengkulu, 2023)
Communal land restoration programs in Ethiopia overlooked the socio-economic context and decision behavior of smallholder farmers for better planning and intervention. Thus, studies related to socio-economic aspects and decision behaviors of smallholder farmers prior to the implementation of communal degraded land restoration are scanty. This study assessed the socio-economic characteristics and decisions making of smallholder farmers in degraded communal land restoration. The kebele under study was purposively selected near the communal degraded land for future intervention. Cross-sectional data were collected from 94 smallholder farmers selected using a systematic random sampling method. Binary logit was employed to see determinants of farmers’ decision to participate in the rehabilitation of communal degraded land. The study result revealed that attitude towards village leaders and labor availability positively determines farmers’ decision, while credit to access and absence of local institutions negatively influence the willingness of farmers to participate in communal land restoration. It seems that the socio-economic base of smallholder farmers did not have a strong linkage for their decision in the land restoration effort. The findings generally suggest that there should be locally based capacity building of the community in a participatory approach for land restoration efforts.